Effects of a multidomain intervention against cognitive decline on dementia risk profiles: results from the AgeWell.de trial - Zülke, Andrea; Pabst, Alexander; Luppa, Melanie; Oey, Anke; Weise, Solveig; Fankhänel, Thomas; Kosilek, Robert Philipp; Schillok, Hannah; Brettschneider, Christian; Czock, David; Frese, Thomas (Alzheimer's and dementia, 2024)
INTRODUCTION Dementia risk scores constitute promising surrogate outcomes for lifestyle interventions targeting cognitive function. We investigated whether dementia risk, assessed using the LIfestyle for BRAin health (LIBRA) index, was reduced by the AgeWell.de intervention. METHODS Secondary analyses of the AgeWell trial, testing a multicomponent intervention (including optimization of nutrition, medication, and physical, social, and cognitive activity) in older adults with increased dementia risk. We analyzed data from n = 461 participants with complete information on risk/protective factors comprised by LIBRA at the 24-month follow-up. Intervention effects on LIBRA and LIBRA components were assessed using generalized linear models. RESULTS The intervention reduced LIBRA scores, indicating decreased dementia risk at follow-up (b = -0.63, 95% confidence interval [CI]: -1.14, -0.12). Intervention effects were particularly due to improvements in diet (odds ratio [OR]: 1.60, 95% CI: 1.16, 2.22) and hypertension (OR: 1.61, 95% CI: 1.19, 2.18). DISCUSSION The AgeWell.de intervention reduced dementia risk. However, several risk factors did not improve, possibly requiring more intensive interventions. Highlights The AgeWell.de intervention reduced dementia risk according to LIfestyle for BRAin health (LIBRA) scores. Beneficial effects on LIBRA are mainly due to changes in diet and blood pressure. A pragmatic lifestyle intervention is apt to reduce dementia risk in an at-risk population.